Decentralized Fixed-Order Piecewise Affine Dynamic Output Feedback Controller Design for Discrete-Time Nonlinear Large-Scale Systems - Wenqiang Ji; Anqing Wang; Jianbin Qiu (IEEE Access, 2017)
This paper proposes a novel decentralized robust H∞ fixed-order dynamic output feedback (DOF) controller design approach for discrete-time nonlinear large-scale systems via Takagi-Sugeno fuzzy-affine models. By a state-input augmentation method and piecewise quadratic Lyapunov functions, some sufficient conditions for decentralized fixed-order piecewise affine DOF controller synthesis are given. It is shown that by some convexification techniques, the controller gains can be obtained by solving a set of linear matrix inequalities. Two simulation examples are carried out to verify the effectiveness of the proposed design method.